Artificial Intelligence Disruption in Islamic Banking Financing Card Products: Regulatory Challenges and Legal Protection Construction in Indonesia: Disrupsi Kecerdasan Artifisial pada Produk Kartu Pembiayaan Perbankan Syariah: Tantangan Regulasi dan Rekonstruksi Perlindungan Hukum di Indonesia - Putra, Bayu Mogana; Wardhani, Adelia Kusuma; Islam, Adikza Nurul (Universitas Islam Indonesia, 2026)
The development of the digital economy and financial technology in Indonesia is driving the use of Artificial Intelligence in Islamic banking financing card products, particularly through credit scoring and auto-underwriting systems. The use of Artificial Intelligence provides efficiency in assessing credit eligibility and analyzing customer risk, but also raises legal issues related to algorithm transparency, potential discriminatory bias, personal data protection, and the accountability of Artificial Intelligence - based decision-making systems. This study aims to analyze the legal regulations regarding the use of Artificial Intelligence in Islamic banking financing card products in Indonesia, as well as to examine the legal challenges and the construction of ideal legal protection for banks and customers. This study uses a normative juridical method with a statutory approach. The legal materials consist of laws and regulations related to Islamic financing, information technology, and personal data protection, the Indonesian Ulema Council Fatwa on financing cards, and various relevant legal literature. The analysis was conducted systematically to construct legal norms related to the use of Artificial Intelligence in Islamic banking. The results indicate that Artificial Intelligence regulations in Islamic banking financing card products in Indonesia are still partial and do not specifically regulate algorithm transparency, Artificial Intelligence oversight, and legal accountability for Artificial Intelligence based financing decisions. Therefore, a hybrid governance model is needed that combines rules-based, principles-driven, and adaptive regulation approaches to create legal certainty, protect customers, and maintain the principles of fairness and sharia compliance in the use of Artificial Intelligence in Islamic banking in Indonesia.